2018
DOI: 10.1016/j.cell.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

CD10+GPR77+ Cancer-Associated Fibroblasts Promote Cancer Formation and Chemoresistance by Sustaining Cancer Stemness

Abstract: Carcinoma-associated fibroblasts (CAFs) are abundant and heterogeneous stromal cells in tumor microenvironment that are critically involved in cancer progression. Here, we demonstrate that two cell-surface molecules, CD10 and GPR77, specifically define a CAF subset correlated with chemoresistance and poor survival in multiple cohorts of breast and lung cancer patients. CD10GPR77 CAFs promote tumor formation and chemoresistance by providing a survival niche for cancer stem cells (CSCs). Mechanistically, CD10GPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
919
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 951 publications
(954 citation statements)
references
References 35 publications
32
919
1
2
Order By: Relevance
“…Ikenaga et al showed the presence of two subpopulations of CAFs in human PDAC stroma (CD10‐positive and CD10‐negative), with the former having a more pro‐tumoural role. Su et al recently confirmed this finding in breast and lung cancers, and demonstrated that a subset of CD10‐positive CAFs (CD10+GPR77+) promote cancer formation and chemoresistance by sustaining cancer stemness. In contrast, we used a ‘without a priori ’ approach, based on the transcriptomic profile of primary cultures to build an assignation, and described distinct phenotypic profiles of CAF subpopulations.…”
Section: Discussionmentioning
confidence: 75%
“…Ikenaga et al showed the presence of two subpopulations of CAFs in human PDAC stroma (CD10‐positive and CD10‐negative), with the former having a more pro‐tumoural role. Su et al recently confirmed this finding in breast and lung cancers, and demonstrated that a subset of CD10‐positive CAFs (CD10+GPR77+) promote cancer formation and chemoresistance by sustaining cancer stemness. In contrast, we used a ‘without a priori ’ approach, based on the transcriptomic profile of primary cultures to build an assignation, and described distinct phenotypic profiles of CAF subpopulations.…”
Section: Discussionmentioning
confidence: 75%
“…An important recent finding is the identification of CD10 and GPR77 as surface markers on CAFs in breast cancer. CD10 + GPR77 + CAFs are predictive for response to chemotherapy and patient survival, particularly in breast tumors with a high grade . The authors showed that the disease‐free survival of breast cancer patients with a high CD10 + GPR77 + CAF infiltration was significantly shorter.…”
Section: Discussionmentioning
confidence: 99%
“…As M2 macrophages express CD206 in hypoxic niches , a virally encoded CD206‐CD3 BiTE could potentially activate T cells in the presence of M2 type TAMs. Recent studies have shed light on the ability of CSCs to communicate with TME components such as CAFs , via exosomes and other secreted factors. A major challenge to many therapies involves overcoming CAF‐mediated effects in the TME, such as their promotion of tumor growth, angiogenesis, extracellular matrix degradation and EMT .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shed light on the ability of CSCs to communicate with TME components such as CAFs , via exosomes and other secreted factors. A major challenge to many therapies involves overcoming CAF‐mediated effects in the TME, such as their promotion of tumor growth, angiogenesis, extracellular matrix degradation and EMT . In recent studies, a fibroblast‐activating protein‐CD3 BiTE has been encoded in an oncolytic vaccinia virus or adenovirus to target immunosuppressive stromal cells .…”
Section: Introductionmentioning
confidence: 99%